Strengthening School Effectiveness Through Collaborative Working : An Evaluation of Training Impact - Pramita, Yushi Widya; Rifameutia, Tjut (Jurnal Paedagogy, 2025)
This study aims to examine the effectiveness of experiential learning-based collaborative working training in enhancing the collaborative competence of stakeholders in elementary school setting. The research participant included of 15 stakeholders, comprising not only school leaders (such as principals and vice principals) but also foundation board members and teacher coordinators at SD X, a private school in Depok. The study employed a one-group pretest-posttest design with a quantitative approach and evaluated outcomes based on three levels of the Kirkpatrick model: reaction, learning, and behavior. The instruments used in this study included a knowledge pretest and posttest, as well as attitude questionnaire. Data analysis techniques consisted of descriptive statistics for the reaction data and non-parametric tests for analyzing the learning outcomes. The results of the reaction evaluation showed a high level of satisfaction with the facilitators and materials, although aspects of the methods and tools need improvement. The learning evaluation, using a Wilcoxon test, revealed a significant difference between pre-test and post-test scores (p = 0.007) with a large effect size (r = 0.693), indicating a significant increase in knowledge. The behavioral evaluation two weeks post-training showed positive attitudinal changes towards collaborative work within the school environment. These findings confirm that experiential learning-based training is effective in improving collaborative understanding and skills, and supports the achievement of school effectiveness in accordance with Marzano’s Model.